INNOVATIVE MECHANISMS OF THE DEVELOPMENT OF SERVICE SECTORS IN SMALL BUSINESS AND PRIVATE BUSINESS SUBJECTS IN DEVELOPED ASIAN COUNTRIES - Mamajonova, Gulnoza (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract. Objective. This article is based on the need to study the foreign experience of developing service sectors in small business and private business entities. The article analyzes the experiences of countries such as China, Japan, and Singapore in this field, innovative ideas, new methods of management and the possibilities of using them. Methods. Analysis, synthesis, and comparative analysis methods were used to achieve the intended goal in the article. Best practices in developed Asian countries, opportunities to implement innovations in our country were discussed. Results. As a result of the research, the possibilities of using innovative mechanisms for the development of service sectors in small business and private business entities in Asian countries were studied. Conclusion. In our country, there was an opportunity to test new opportunities for the development of service sectors in small business and private business entities.